DINAMIKA PROSA INDONESIA PERIODE 1920–2000 DALAM REPRESENTASI IDENTITAS, IDEOLOGI, DAN MODERNITAS - Muyassaroh Muyassaroh (Cakrawala Indonesia, 2025)
The development of Indonesian prose from 1920 to 2000 reflects the cultural and historical dynamics of the nation over nearly a century. This study aims to explore the representation of identity, ideology, and modernity in prose works across various literary periods, including the colonial era, independence, Old Order, New Order, and Reform era. Employing a literary historiography approach, this research examines the correlation between socio-political contexts and the narrative forms and themes produced. The findings reveal that each period demonstrates distinct aesthetic and thematic tendencies. The 1920s–1940s were characterized by a spirit of nationalism and identity formation; the 1950s–1970s emphasized ideological tensions and moral discourse; while the 1980s–2000s exhibited stylistic diversity and more complex individual and social issues. This study asserts that Indonesian prose is not merely an artistic product but also a historical document that records the transformation of values and collective consciousness. It contributes to the mapping of Indonesian literary historiography by emphasizing the importance of reading prose as a dynamic reflection of socio-cultural change.